Answer
![\frac{(x+8)^2}{4^{}}-\frac{(y-4)^2}{36^{}}=1](https://img.qammunity.org/2023/formulas/mathematics/college/vxy6n4tqo5xo7mmb6ymm1fqtgtx396awp5.png)
Step-by-step explanation
Since the transverse axis is parallel to the x-axis, this hyperbola opens left/right.
Coordinate of the center, (h, k) = (-8, 4)
The length of the transverse axis = 4 units. This implies that,
a = 4/2 = 2 and b = 12/2 = 6
Please note that the equation of a hyperbola is
![(\mleft(x-h\mright)^2)/(a^2)-((y-k)^2)/(b^2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/qv5b2j21tfp6rg1q6yqoutb7to8j9qjbwj.png)
This implies
![\begin{gathered} (\mleft(x--8\mright)^2)/(2^2)-((y-4)^2)/(6^2)=1 \\ \frac{(x+8)^2}{4^{}}-\frac{(y-4)^2}{36^{}}=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6axjdrorpyxnrzggd12y8ho79dfjfk65s4.png)